2008
DOI: 10.1364/oe.16.001975
|View full text |Cite
|
Sign up to set email alerts
|

Robust flow measurement with multi-exposure speckle imaging

Abstract: Laser Speckle Contrast Imaging (LSCI) is a minimally invasive full field optical technique used to generate blood flow maps with high spatial and temporal resolution. The lack of quantitative accuracy and the inability to predict flows in the presence of static scatterers such as an intact or thinned skull have been the primary limitation of LSCI. We present a new Multi-Exposure Speckle Imaging (MESI) instrument that has potential to obtain quantitative baseline flow measures. We show that the MESI instrument … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
395
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
3
1

Relationship

3
7

Authors

Journals

citations
Cited by 314 publications
(420 citation statements)
references
References 28 publications
(17 reference statements)
10
395
0
2
Order By: Relevance
“…[10][11][12][13][14] Recent advances in LSCI termed multiexposure speckle imaging (MESI) have allowed for the technique to move from primarily acute experiments to chronic studies through improvements in its quantitative accuracy of blood flow measurements. 15 By using multiple camera exposures spanning almost three decades in duration and improved mathematical models, MESI is able to more precisely sample and map the flow distributions prevalent in the rodent vasculature. 16 Studies have shown MESI to accurately estimate a wide range of flows in vivo, including complete flow reduction during middle cerebral artery occlusions, 17 and also shows the ability to determine spatially integrated perfusion measurements from unresolvable microvasculature within the parenchyma.…”
Section: Introductionmentioning
confidence: 99%
“…[10][11][12][13][14] Recent advances in LSCI termed multiexposure speckle imaging (MESI) have allowed for the technique to move from primarily acute experiments to chronic studies through improvements in its quantitative accuracy of blood flow measurements. 15 By using multiple camera exposures spanning almost three decades in duration and improved mathematical models, MESI is able to more precisely sample and map the flow distributions prevalent in the rodent vasculature. 16 Studies have shown MESI to accurately estimate a wide range of flows in vivo, including complete flow reduction during middle cerebral artery occlusions, 17 and also shows the ability to determine spatially integrated perfusion measurements from unresolvable microvasculature within the parenchyma.…”
Section: Introductionmentioning
confidence: 99%
“…Progress has been made in establishing a flow decorrelation time using laser speckle contrast techniques [117]; however, issues still remain of how to relate this time constant to the flow velocity [118]. Although accurate absolute measurements RBC V cannot be calculated, perfusion changes can be successively monitored and tracked.…”
Section: Laser Speckle Imagingmentioning
confidence: 99%
“…While LSCI permits sensitive mapping of blood flow in surface vessels, the exact quantitative relationship between speckle contrast and blood flow velocity remains undefined (Duncan & Kirkpatrick, 2008). LSCI is susceptible to experimental artifacts that can vary between animals and imaging sessions (Parthasarathy et al, 2008;Ayata et al, 2004) and is best restricted to describing relative changes in the pattern of blood flow rather than quantifying blood flow velocity (Parthasarathy et al, 2008;Ayata et al, 2004).…”
Section: Laser Speckle Contrast Imaging (Lsci)mentioning
confidence: 99%